The terminologies of automobiles: translation problems (Texas Journal of Multidisciplinary Studies, 2023)
The article studies the main problems of the translation of scientific-technical terminology in context of mechanical engineering and its elimination. It is necessary to work on translation, using various exercises, focused on production of translation skill from native language into English, or on the contrary.